Public Law Sources and Analogies of International Law - Bjorge, Eirik (Victoria University of Wellington Law Review, 2018)
Are the "general principles of law recognised by civilized nations" capable of adjusting to the progress and needs of the international community? This article argues that they are, and that international law needs, to a larger degree than what has been the case, to draw on principles of public law. Those principles of public law are not to supplant, but to supplement, those of private law. The article analyses four principles: the principle of legality; the principle requiring positive legal basis for state action; the principle that even the highest emanation of the executive power cannot escape judicial review; and the principle of protection of legitimate expectations. If one takes account of the needs of international law, there is no reason whatever why today we should accede to the orthodoxy that the intention behind the concept of general principles is only to authorise a court to apply the general principles of municipal jurisprudence, in particular of private law, in so far as they are applicable to relations of states – if for no other reason than the fact that international law no longer governs only relations of states.